X‐ray and DFT‐calculated structures of bis[N‐(quinolin‐8‐yl)benzamidato‐κ2N, N′]copper(II). Issue 3 (25th February 2016) - Chatturgoon, Teshica; Akerman, Matthew P.
Abstract : The solid‐state structure of a neutral copper(II) chelate is reported. The molecule crystallizes as discrete dimers stabilized by weak C—H…O interactions. Density functional theory (DFT) simulations are used to probe the stability of the dimeric structures. The lowest energy gas‐phase structure of the monomer has higher point symmetry than the solid‐state structure. Abstract : The application of transition metal chelates as chemotherapeutic agents has the advantage that they can be used as a scaffold around which ligands with DNA recognition elements can be anchored. The facile substitution of these components allows for the DNA recognition and binding properties of the metal chelates to be tuned. Copper is a particularly interesting choice for the development of novel metallodrugs as it is an endogenous metal and is therefore less toxic than other transition metals. The title compound, [Cu(C16 H11 N2 O)2 ], was synthesized by reacting N ‐(quinolin‐8‐yl)benzamide and the metal in a 2:1 ratio. Ligand coordination required deprotonation of the amide N—H group and the isolated complex is therefore neutral. The metal ion adopts a flattened tetrahedral coordination geometry with the ligands in a pseudo‐ trans configuration. The free rotation afforded by the formal single bond between the amide group and phenyl ring allows the phenyl rings to rotate out‐of‐plane, thus alleviating nonbonded repulsion between the phenyl rings and the quinolyl groups within the complex. Weak C—H…O interactions stabilize a dimer in the solid state. Density functional theory (DFT) simulations at the PBE/6‐311G(dp) level of theory show that the solid‐state structure ( C 1 symmetry) is 79.33 kJ mol −1 higher in energy than the lowest energy gas‐phase structure ( C 2 symmetry). Natural bond orbital (NBO) analysis offers an explanation for the formation of the C—H…O interactions in electrostatic terms, but the stabilizing effect is insufficient to support the dimer in the gas phase.